PENGARUH SUMBER PUPUK NITROGEN TERHADAP KUANTITAS DAN KUALITAS BENIH LIMA KULTIVAR WIJEN (Sesamum indicum L.) - , TRIASIH S K, Dr. Ir. Taryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the problems in organic farming is the lack of organic seed availability. Organic seed is seed that was produced in organic farming. Soil is one of the factors that determine the success of sesame cultivation and to get an optimal growth with high yield, nitrogen in sufficient quantities is needed to improve the growth of roots, stems and leaves. Nitrogen can be found in organic or inorganic fertilizer. The aims of the study were to know the effects of different sources of nitrogen fertilizer (organic and inorganic) on the quality and quantity of sesame seeds and to know the cultivar that can be grown and produce well in the organic farming systems. This study used a completely randomized design (CRD) factorial with three replications. The first factor are 5 cultivars of sesame namely Sumberejo 1, Sumberejo 3, Lokal Hitam, Lokal Putih and Purworejo. The second factor are the sources of the nitrogen fertilizer that were control (without addition of organic or inorganic fertilizer), the addition of inorganic fertilizer (150 kg/ha) and the addition of organic fertilizer (8,6 ton/ha). The result showed that in the soil with high organic matter, nitrogen fertilizer (organic and inorganic) did not influence on the quantity of sesame seeds, but on seed quality, reduce the oil content and germination percentage of sesame seeds. Sesame cultivars that were used (Sumberejo 1, Sumberejo 3, Lokal Hitam, Lokal Putih, Purworejo) could grow well but not been able to produce optimally.